Integrated Tourism Marketing Communication at Makassar International Festival & Forum (F8) - Lambe, Pearly Claire Christabella; Husain, A. Hasan Al (PT FORMOSA CENDEKIA GLOBAL, 2024)
Makassar International Eight Festival and Forum (F8) is one of the biggest events in Makassar City which was first held on September 8 2016 at the Losari Beach Pavilion. This festival covers eight creative sectors, namely: Film, Fashion, Fiction Writer & Font, Fine Arts, Food & Fruit, Fusion Music, Flora & Fauna. After being absent in 2020 and 2021 due to the COVID-19 pandemic, F8 was held again and was successfully included in the Top 10 Kharisma Events Nusantara (KEN) in 2022 and 2023. This research aims to apply promotional aspects carried out by the Makassar City Tourism Office heading to the F8 Festival. The method used is descriptive qualitative, with data collection through interviews and observation. The research results show that F8 not only functions as an annual festival, but also as an effective strategic promotional mix tool with a focus on collaborating aspects of advertising and personal sales. Advertising is carried out through social media and conversion media, as well as personal sales which are packaged in a business to business form. Collaboration with various parties and friendly countries also supports improving the image of Makassar City as an international destination. In this way, F8 not only succeeded in increasing tourist visits, but also strengthened bilateral relations and promoted the local culture of Makassar City on the international stage